Прогноз динаміки макроекономічних показників - Poveshchenko, G. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The known mathematical models of the macroeconomic dynamics are added by the developed model of labour market in Ukraine. The obtained system of differential equations is used as a basis of the program for forecasting calculations of macroeconomic parameter dynamics. Examples of a middleterm forecasting of national economy macrodynamics are given.